Management of very early-onset fetal growth restriction: results from 92 consecutive cases - Hoellen, Friederike; Bohlmann, Michael K. (In vivo, 2016)
Aim: To evaluate management of early-onset intrauterine growth restriction (IUGR) and to define outcome according to obstetric setting. Patients and Methods: During an 11-year period (2000-2011), data of patients presenting with IUGR and preterm delivery of less than 30 weeks of gestation at a tertiary perinatal center were retrospectively reviewed. Results: A total of 92 pregnancies were investigated. Delivery was indicated for fetal reasons in 38 out of 92 patients. Sixteen children of our cohort died within one year post partum, out of which eight had suffered from severe early-onset IUGR causing iatrogenic preterm delivery. Concerning the fetal outcome, gestational age at delivery and antenatal exposure to corticosteroids were found to be crucial. Conclusion: In some cases, respiratory distress syndrome prophylaxis and a “wait and see” approach to management in favor of a prolongation of the pregnancy might be favorable. Randomized prospective trials in early-onset IUGR with threatened preterm deliveries are needed in order to define guidelines for an individually tailored management of early-onset preterm infants.
Gesehen am 23.05.2019